2017
DOI: 10.1007/s11882-017-0713-2
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Causes of Anaphylaxis

Abstract: Multiple new and elusive causes of anaphylaxis have been described over the past 35 years. Further research is required to identify the epidemiology, pathophysiology, and clinical impact of these hidden causes. Although these culprits should be considered in the appropriate clinical scenarios, many remain exceedingly rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 95 publications
0
3
0
1
Order By: Relevance
“…The various symptoms of mustard allergy that have been observed over the years are mainly mucocutaneous manifestations (urticaria, angioedema, hoarse voice); respiratory symptoms (wheezing, bronchospasm, recurrent cough, nasal congestion, chest tightness, angioedema); gastrointestinal manifestations (epigastralgia, nausea, vomiting, diarrhea, abdominal pain); cardiovascular manifestations (tachycardia, hypotension, chest pain) [4]. Mustard includes irritants such as isothiocyanates that can cause contact dermatitis following non-immunological basophil degranulation without IgE involvement; a reaction with superficial necrosis has been observed in 5% of cases [6]. The best resource for determining the likelihood of a hidden allergen causing an allergic reaction is to take a detailed history of the allergic reaction, the presence of cofactors (medication, physical exertion), the suspected food, the type of food and where it was consumed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The various symptoms of mustard allergy that have been observed over the years are mainly mucocutaneous manifestations (urticaria, angioedema, hoarse voice); respiratory symptoms (wheezing, bronchospasm, recurrent cough, nasal congestion, chest tightness, angioedema); gastrointestinal manifestations (epigastralgia, nausea, vomiting, diarrhea, abdominal pain); cardiovascular manifestations (tachycardia, hypotension, chest pain) [4]. Mustard includes irritants such as isothiocyanates that can cause contact dermatitis following non-immunological basophil degranulation without IgE involvement; a reaction with superficial necrosis has been observed in 5% of cases [6]. The best resource for determining the likelihood of a hidden allergen causing an allergic reaction is to take a detailed history of the allergic reaction, the presence of cofactors (medication, physical exertion), the suspected food, the type of food and where it was consumed.…”
Section: Discussionmentioning
confidence: 99%
“…The best resource for determining the likelihood of a hidden allergen causing an allergic reaction is to take a detailed history of the allergic reaction, the presence of cofactors (medication, physical exertion), the suspected food, the type of food and where it was consumed. Skin testing as a first line of defense; using native foods such as ground and suspended mustard seed or mustard oil; a papule at 8 mm would have a sensitivity of 50% and specificity of 90% [6]. Mustard seeds may be contaminated with moulds or mites and therefore a risk of false-positive results [4].…”
Section: Discussionmentioning
confidence: 99%
“…Los informes de anafilaxia a animales peludos son extremadamente raros, con pocos casos reportados en la literatura, especialmente a caballo y gato (57). El látex es más comúnmente conocido como un alérgeno de contacto en el ámbito ocupacional, sin embargo se han documentado casos de anafilaxia por exposición al látex, ya sea en el contexto peri-anestésico (58) o incluso por alimentos preparados con guantes de látex (59).…”
Section: Causasunclassified
“…The authors reported these as examples of “hidden” allergens in composite foods, and linked their occurrence to their relatively recent introduction into the Norwegian diet. Nanagas et al undertook a wide-ranging review of hidden allergens, which included non-foods including such as aluminum and also some so-called exotic foods such as crocodile, sago worms (8). New foods and food trends mean that many meals eaten are composite meals, the composition of which might be difficult to elicit.…”
Section: Introductionmentioning
confidence: 99%